Liberalized and neglected? : food marketing policies in Eastern Africa - Seppälä, Pekka; World Institute for Development Economics Research; United Nations University (World development studies, 1998)
Abstract (s. xiii).
Keywords: ruoka; Food; Marketing; elintarvikepolitiikka; elintarvikkeet; markkinointi; Afrikka; Africa; Itä-Afrikka; Malawi; Tanzania; Kenya